2018
DOI: 10.1038/s41533-018-0108-4
|View full text |Cite
|
Sign up to set email alerts
|

IMP2ART systematic review of education for healthcare professionals implementing supported self-management for asthma

Abstract: Despite a robust evidence base for its effectiveness, implementation of supported self-management for asthma is suboptimal. Professional education is an implementation strategy with proven effectiveness, though the specific features linked with effectiveness are often unclear. We performed a systematic review of randomised controlled trials and controlled clinical trials (published from 1990 and updated to May 2017 using forward citation searching) to determine the effectiveness of professional education on as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Implementation remains challenging. Pressures of time, organisational barriers, 53 and the need to develop professional skills, 54 as well as negative views about the usefulness of action plans, 55 56 57 are barriers to adoption of supported self-management into routine clinical practice. Our findings suggest that initiatives that facilitate regular review (including mobile phone and internet interventions), 58 ensure that reviews are appropriate (for example, to cultural needs), 59 or involve non-medical or peer support 60 may offer promise for future implementation and research endeavours.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation remains challenging. Pressures of time, organisational barriers, 53 and the need to develop professional skills, 54 as well as negative views about the usefulness of action plans, 55 56 57 are barriers to adoption of supported self-management into routine clinical practice. Our findings suggest that initiatives that facilitate regular review (including mobile phone and internet interventions), 58 ensure that reviews are appropriate (for example, to cultural needs), 59 or involve non-medical or peer support 60 may offer promise for future implementation and research endeavours.…”
Section: Discussionmentioning
confidence: 99%
“…All these are modifiable barriers. Team-based, comprehensive training of HCPs including nurses, assistant medical officers, and assistant pharmacists in performing-or supporting-asthma self-management counselling may not only facilitate asthma self-management 13,[29][30][31][32] but also help overcome the resource limitations. Only some HCPs were able to attend the structured training relating to asthma self-management in the hope that they would share their learning with their peers who had stayed back to carry out clinic duties.…”
Section: Discussionmentioning
confidence: 99%
“…18 The authors acknowledge that the behaviours identified in this study may not meet the health psychology definitions of 'habit'. Nonetheless, habit formation has been demonstrated as beneficial in recognising and addressing behaviour change in long-term conditions, 9 and was found to be a useful theory to help interpret the present findings and offer practical implications for how to optimise the delivery of supported self-management.…”
Section: Strengths and Limitationsmentioning
confidence: 81%
“…19,26 For example, strategies offering advice in how (not just why) to change habitual behaviour 19 and avoiding contextual cues that trigger a 'bad' habit are widely recommended, 26,29 but the success of these approaches in the context of SABA use will require further research. The importance of training healthcare professionals to use behaviour change techniques has already been demonstrated; 9 data from the present…”
Section: Helpingmentioning
confidence: 82%
See 1 more Smart Citation